KEPUASAN KERJA PERAWAT - Husin Husin (Jurnal Medika : Karya Ilmiah Kesehatan, 2017)
Background : Job satisfaction is one the important factors tobe considered by the organization. This is because the satisfaction feeling of the employees on the job will minimize the high rate of employee turnover and absenteeism and increase productivity and employee loyalty to the organization. Aim : To find out how the job satisfaction of nurse based on the hygiene factor and pemotivation factor was in the Ismic Hospital Samarinda. Method : Based hygiene factor of this research, it is known that employees at the Islamic Hospital Samarinda satisfied as much as 25.8% and 74.2% are not satisfied. While pemotivation factor of 58.3% who said they were satisfied and dissatisfied as much as 41.7%, on performance and job satisfaction of nurses at the Islamic Hospital Samarinda 0.00 p-value < from 0.05 alpha value means the distribution of nurse job satisfaction variables abnormally shaped. Result : Type in this research is descriptive. This research of thesis uses the cross sectional draff. Sa,pling technique that us is random sampling that quantity are 120 responden. This research has done on 18-25 of April 2016. The data have collected by quisiners Conclusion : This hospital management should do an evaluation of the existing payroll system to give salary according to age, gender, education, tenure, responsibilities and job performance of employees.